Mesityllithium - Mhaske, Santosh B. (Synlett, 2005)

Chemistry of recently isolated naturally occurring quinazolinone alkaloids - Mhaske, Santosh B.; N. P. Argade (Tetrahedron, 2006)
The present review portrays a concise account of the isolation, bioactivity, and synthesis of bioactive quinazolinone-based natural products for the period 1983-2005 and the recent developments in the area of complex quinazolinone natural products with a special emphasis on new synthetic routes and strategies. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: 1983-2005; bioactivity; concise account; isolation; natural quinazolinones; synthesis

Hexamethyldisilazane-iodine induced intramolecular dehydrative cyclization of diamides: a general access to natural and unnatural quinazolinones - Kshirsagar, Umesh A.; Mhaske, Santosh B.; N. P. Argade (Tetrahedron Letters, 2007)
A simple and efficient general approach to various quinazolinone scaffolds, including peptidomimetic examples, has been demonstrated by employing HMDS/I-2 for the intramolecular dehydrative cyclization of diamides. The protecting groups -Boc, -Fmoc and -Cbz tolerated the present reaction conditions and we did not observe any racemization. The present protocol has also been used as a key step for the efficient four-step syntheses of the naturally occurring quinazolinones, sclerotigenin, (-)-circumdatin-F and (-)-fumiquinazoline-F. (c) 2007 Elsevier Ltd. All rights reserved.
Keywords: diamides; HMDS/I-2; intramolecular dehydrative cyclizations; natural and unnatural quinazolinones; synthesis

Pd-Catalyzed imine cyclization: synthesis of antimalarial natural products aplidiopsamine A, marinoquinoline A, and their potential hybrid NCLite-M1 - Mahajan, Jyoti P.; Suryawanshi, Yogeshwar R.; Mhaske, Santosh B. (Organic Letters, 2012)
Palladium-catalyzed cyclization of imines has been developed to construct the extremely rare 3H-pyrrolo[2,3-c]quinoline ring system for diversity oriented first total synthesis of antimalarial marine natural product Aplidiopsamine A as well as synthesis of Marinoquinoline A and potential natural product hybrid NCLite-M1.

Direct allylation of in situ generated aldehyde acyl anions by synergistic NHC and palladium catalysis - Ahire, Milind M.; Mhaske, Santosh B. (Angewandte Chemie-International Edition, 2014)
The direct regioselective allylation of in situ generated aldehyde acyl anions has been achieved by synergistic NHC and Pd catalysis. It provides an efficient access to valuable beta,gamma-unsaturated ketones under mild reaction conditions starting from easily accessible allylic carbonates and aldehydes without any preactivation. The synergistic catalysis method demonstrated herein adds a new dimension to the area of metal-mediated C allylation.
Keywords: aldehyde umpolung; C allylation; N-heterocyclic carbenes; Palladium; synergistic catalysis

Protecting-group-free diastereoselective total synthesis of (+/-)-6-epi-cleistenolide and chemoenzymatic synthesis of (-)-6-epi-cleistenolide - Mahajan, Pankaj S.; Gonnade, Rajesh G.; Mhaske, Santosh B. (European Journal of Organic Chemistry, 2014)
A short, efficient, practical, and protecting-group-free diastereoselective total synthesis of (+/-)-6-epi-cleistenolide (1) has been achieved in five steps in 60% overall yield. The use of a chemoenzymatic approach also gave (-)-6-epi-cleistenolide (1) (>99.9% ee). The Achmatowicz reaction, chemoselective oxidation of a hemiacetal, diastereoselective 1,3-anti reduction of alpha-hydroxy ketone, and enzymatic resolution of a 1,3-diol are the key features of this linear total synthesis. The synthetic strategy demonstrated in this paper could be extended for an asymmetric total synthesis of (-)-cleistenolide (1) and related biologically active natural products.
Keywords: Asymmetric synthesis; diastereoselectivity; Enzyme catalysis; Lipases; Oxygen heterocycles; Total synthesis

Transition-metal-free C-S bond formation: a facile access to aryl sulfones from sodium sulfinates via arynes - Pandya, Virat G.; Mhaske, Santosh B. (Organic Letters, 2014)
Sulfones have been attractive targets for synthetic organic chemists owing to their immense applications in medicinal, material, and synthetic chemistry. In this context, an efficient transition-metal-free process has been demonstrated, wherein a broad range of alkyl/aryl/heteroaryl sodium sulfinates react with varyingly substituted aryne precursors (o-silyl aryl triflates) under mild reaction conditions to afford structurally diverse sulfones in good to excellent yields.

Ammonium persulfate activated DMSO as a one-carbon synthon for the synthesis of methylenebisamides and other applications - Mahajan, Pankaj S.; Tanpure, Subhash D.; More, Namita A.; Gajbhiye, Jayant M.; Mhaske, Santosh B. (RSC Advances, 2015)
Activation of DMSO to work as an economical and environmentally benign one-carbon synthon has been achieved by using a bench-top reagent ammonium persulfate for general and efficient access to symmetrical methylenebisamides from primary amides. This methodology was used to achieve a three-component Mannich reaction using acetophenone, saccharin and DMSO to furnish a beta-amino ketone. It also provided a metal-free synthesis of thiadiazole and bis(phenyl)methane. Effectively, this method uses DMSO as a safer surrogate to formaldehyde. A mechanism for methylenebisamide formation involving radical intermediates has been proposed based on mechanistic studies.

Radical-mediated dehydrative preparation of cyclic imides using (NH4)(2)S2O8-DMSO: application to the synthesis of vernakalant - Garad, Dnyaneshwar N.; Tanpure, Subhash D.; Mhaske, Santosh B. (Beilstein Journal of Organic Chemistry, 2015)
Ammonium persulfate-dimethyl sulfoxide (APS-DMSO) has been developed as an efficient and new dehydrating reagent for a convenient one-pot process for the synthesis of miscellaneous cyclic imides in high yields starting from readily available primary amines and cyclic anhydrides. A plausible radical mechanism involving DMSO has been proposed. The application of this facile one-pot imide forming process has been demonstrated for a practical synthesis of vernakalant.
Keywords: APS-DMSO; imides; practical synthesis; radical-mediated; vernakalant

Total and semi-syntheses of antimicrobial thuggacin derivatives - Franke, Jana; Bock, Martin; Dehn, Richard; Fohrer, Joerg; Mhaske, Santosh B.; Migliorini, Antonella; Kanakis, Argyrios A.; Jansen, Rolf; Herrmann, Jennifer; Mueller, Rolf; Kirschning, Andreas (Chemistry-A European Journal, 2015)
The total and semi-synthesis of 13 new macrolactones derived from thuggacin, which is a secondary metabolite from the myxobacterium Sorangium cellulosum, are reported. The thuggacins have attracted much attention due to their strong antibacterial activity, particularly towards Mycobacterium tuberculosis. This study focuses on 1) thuggacin derivatives that cannot equilibrate by transacylation between the three natural thuggacins A-C, 2) the roles of the thiazole ring, and 3) the hexyl side chain at C2. Semi-synthetic O-methylation at C17 suppressed the transacylations without a substantial loss of antibacterial activity. Exchanging the C17-C25 side chain for simplified hydrophobic chains led to complete loss of antibacterial activity. Exchange of the thiazole by an oxazole ring or removal of the hexyl side chain at C2 had no substantial effect on the biological properties.
Keywords: antibiotics; lactones; Natural products; synthesis design; Total synthesis

Nucleophilic nitration of arynes by sodium nitrite and its multicomponent reaction leading to double-functionalized arenes - Dhokale, Ranjeet A.; Mhaske, Santosh B. (Organic Letters, 2016)
An unusual nucleophilic nitration of arynes by NaNO2 in the presence of water has been developed, and the concept was further demonstrated to accomplish a double functionalization of arynes using a multicomponent reaction protocol to synthesize pharmaceutically important (2-nitrophenyl)methanol derivatives. Such substitution ortho to -NO2 is difficult by other means. The reaction conditions are mild and avoid the use of strong acids, expensive transition metal catalysts, and additives.

Pd(II)-catalyzed intramolecular tandem olefin amidation/C-H activation protocol for the syntheses of the protoberberine class of natural products - Garad, Dnyaneshwar N.; Mhaske, Santosh B. (Organic Letters, 2016)
A Pd(II)-catalyzed intramolecular tandem olefin amidation/C-H activation protocol has been developed for the synthesis of an 8-oxoprotoberberine core. It was successfully applied for the syntheses of (+/-)-8-oxocanadine, (+/-)-8-oxotetrahydropalmitine, and (+/-)-8-oxostylopine, which can be easily converted to the respective protoberberine natural products. The short synthetic route demonstrated would be useful for the synthesis of a large number of natural products and their analogues featuring a protoberberine scaffold.

Radical beckmann rearrangement and its application in the formal total synthesis of antimalarial natural product isocryptolepine via C-H activation - Mahajan, Pankaj S.; Humne, Vivek T.; Tanpure, Subhash D.; Mhaske, Santosh B. (Organic Letters, 2016)
The Beckmann rearrangement of ketoximes, mediated by ammonium persulfate-dimethyl sulfoxide as a reagent, has been achieved under neutral conditions. Based on the radical trapping and O-18-labeling experiments, the transformation follows a mechanism involving a radical pathway. The scope and generality of the developed protocol has been demonstrated by 19 examples. The developed protocol and Pd-catalyzed intramolecular double C-H activation were used as key steps in the formal total synthesis of antimalarial natural product isocryptolepine.

Switch-on NIR probe for specific detection of Hg2+ ion in aqueous medium and in mitochondria - Agarwalla, Hrideshg; Mahajan, Pankaj S.; Sahu, Debashis; Taye, Nandaraj; Ganguly, Bishwajit; Mhaske, Santosh B.; Chattopadhyay, Samit; Das, Amitava (Inorganic Chemistry, 2016)
A new 4,4-difluoro-4-bora-3a,4a-diaza-s-indacene (BODIPY)-based probe molecule (L) is synthesized for specific binding to Hg2+ ion in physiological condition with an associated luminescence ON response in the near-IR region of the spectrum. Appropriate functionalization in the 5-position of each of two pyrrole moieties with styryl functionality in a BODIPY core helped us in achieving the extended conjugation and a facile intramolecular charge transfer transition with a narrow energy gap for frontier orbitals. This accounted for a poor emission quantum yield for the probe molecule L. Binding to. Hg2+ helped in interrupting the facile intramolecular charge transfer (ICT) process that was initially operational for L. This resulted in a hypsochromic shift of absorption band and a turn-on luminescence response with lambda(Em)(max) of 650 nm on specific binding to Hg2+. Observed spectral changes are rationalized based on quantum chemical calculations. Interestingly, this reagent is found to be localized preferentially in the mitochondria of the live human colon cancer (Hct116) cells. Mitochondria is one of the major targets for localization of He2+, which actually decreases the mitochondrial membrane potential and modifies various proteins having sulfudryl functionality(ies) to cause cell apoptosis. Considering these, ability of the present reagent to specifically recognize Hg2+] in the mitochondrial region of the live Hct116 cells has significance.

Achmatowicz reaction: A versatile tool in bioactive natural products synthesis - Mahajan, Pankaj S.; Humne, Vivek T.; Mhaske, Santosh B. (Current Organic Chemistry, 2017)
Achmatowicz reaction has emerged as an efficient tool in organic synthesis since its discovery in 1971 by Achmatowicz Jr. The original protocol went through several advantageous variations. Biocatalytic and metal catalyzed versions of this reaction are some of the significant achievements, which further enhanced its effectiveness. The pyranone product of the Achmatowicz reaction is a versatile building block for the synthesis of bioactive scaffolds, drugs and natural products. The present review covers the application of the Achmatowicz reaction in the synthesis of natural products and bioactive molecules reported from 1971 to date. It has been divided into seven sections on the basis of the core structures of the natural products synthesized utilizing the Achmatowicz reaction. We believe that this comprehensive review will attract many more organic chemists to explore its utility in organic synthesis, especially in the synthesis of bioactive natural products as well as drugs in their efficient and atom economical synthesis.
Keywords: Achmatowicz reaction; carbohydrates; Furanols; Natural products; pyranones; Total synthesis

Diversification of quinazolinones by Pd-catalyzed C(sp(3))-acetoxylation - Garad, Dnyaneshwar N.; Mhaske, Santosh B. (Journal of Organic Chemistry, 2017)
The quinazolinone ring has been exploited as a directing group for C(sp(3))-H functionalization for the first time. The proximal C-gamma(sp3)-H bonds have been oxidized by palladium-catalyzed acetoxylation reaction. Various functional groups on the quinazolinone scaffold were tolerated to provide novel quinazolinone derivatives. The use of base was found to be crucial for the mono selective acetoxylations.

Diversity-oriented synthesis of spiroannulated benzofuran-3-one scaffold of leptosphaerin C and congeners via aryne insertion - Dhokale, Ranjeet A.; Mhaske, Santosh B. (Journal of Organic Chemistry, 2017)
A concise synthesis of functionalized cyclohexenone-fused spirobenzofuran-3-ones under mild reaction conditions was developed. The reaction proceeds via insertion of aryne into the C-O bond followed by a regioselective intramolecular conjugate addition. The use of silyl-protected acid was crucial for the transformation. This protocol was successfully applied for the synthesis of leptosphaerin C core and its novel analogues.

Pd-catalyzed regioselective mono-arylation: quinazolinone as the inherent directing group for C(sp(2))-H activation - Garad, Dnyaneshwar N.; Viveki, Amol B.; Mhaske, Santosh B. (Journal of Organic Chemistry, 2017)
The Pd-catalyzed quinazolinone-directed regioselective monoarylation of aromatic rings by C-H bond activation is developed. A broad substrate scope is demonstrated for both quinazolinone as well as diary-liodonium triflates. The use of a base was found to be crucial for this transformation, unlike for the known nitrogen-directed arylations. All of the novel quinazolinones of biological interest were synthesized by using the operationally simple Pd(II)-catalyzed arylation reaction.
Keywords: Aromatic rings; catalysis; Chemical activation; Chemical reactions; Palladium compounds; Regioselectivity

Synthesis and biological evaluation of new fluconazole β-lactam conjugates linked via 1,2,3-triazole - Divse, Jaisingh M.; Mhaske, Santosh B.; Charolkar, Chaitanya R.; Sant, Duhita G.; Tupe, Santosh G.; Deshpande, Mukund V.; Khedkar, Vijay M.; Nawale, Laxman U.; Sarkar, Dhiman; Pore, Vandana S. (New Journal of Chemistry, 2017)
Novel 1,2,3-triazole-linked β-lactam–fluconazole conjugates 12(a–l) were designed and synthesized. The compounds showed potent antifungal activity against two pathogenic Candida strains; Candida albicans ATCC 24433 and Candida albicans ATCC 10231 with MIC values in the range of 0.0625–2 μg mL−1. Compounds 12h, 12j and 12k showed promising antifungal activity against all the tested fungal pathogens except C. neoformans ATCC 34554 compared to fluconazole. Compound 12j in which the β-lactam ring was formed using para-anisidine and benzaldehyde was found to be more potent than fluconazole against all the fungal strains with an IC50 value of <0.015 μg mL−1 for Candida albicans (ATCC 24433). Mechanistic studies for active compounds revealed that the antifungal action was due to ergosterol inhibition. Compounds 12h and 12j at a concentration of 0.125 μg mL−1 caused 91.5 and 96.8% ergosterol depletion, respectively, compared to fluconazole which at the same concentration caused 49% ergosterol depletion. The molecular docking study revealed that all the fluconazole β-lactam conjugates 12(a–l) could snugly fit into the active site of lanosterol 14α-demethylase (CYP51) with varying degrees of affinities. As anticipated, the binding energy for compound 12j (−58.961 kcal mol−1) was much smaller than that for fluconazole (−52.92 kcal mol−1). The synthesized compounds have therapeutic potential for the control of candidemia.

Synthesis of methyl-protected (+/-)-chlorizidine A - Mahajan, Jyoti P.; Mhaske, Santosh B. (Organic Letters, 2017)
The first total synthesis of the methyl-protected (+/-)-chlorizidine A has been achieved in 10 steps. Pd-catalyzed decarboxylative coupling and late-stage oxidation were utilized to, construct the 5H-pyrrolo[2,1-a]isoindol-5-one scaffold. Samarium(II) iodide mediated Reformatsky reaction and intramolecular Mitsunobu reactions were efficiently applied for the synthesis of the 2,3-dihydropyrrolizine ring system. Chlorizidine A is highly prone to degradation; hence, methyl-protected (+/-)-chlorizidine A was prepared.

Synthesis of o-methyl trifluoromethyl sulfide substituted benzophenones via 1,2-difunctionalization of aryne by insertion into the C-C bond - Ahire, Milind M.; Khan, Ruhima; Mhaske, Santosh B. (Organic Letters, 2017)
An efficient process for the preparation of valuable o-methyl trifluoromethyi sulfide substituted benzopheriones has been developed. The transition-metal-free method features insertion of aryne into a C-C sigma-bond under mild reaction conditions for the first time to achieve ortho-difunctionalized arenes containing a pharmaceutically important trifluoromethylthio functional group. A wide substrate, scope has been demonstrated for the developed protocol.

Synthesis of succinimide derivatives by NHC-catalyzed stetter reaction of aromatic aldehydes with N-substituted itaconimides - Ahire, Milind M.; Mhaske, Santosh B. (ACS Omega, 2017)
An N-heterocyclic carbene-catalyzed intermolecular Stetter reaction of aromatic aldehydes with N-substituted itaconimides has been developed. A delicate balance between the Stetter reaction and the competing isomerization of the itaconimide double bond has been achieved in this operationally simple reaction to afford valuable new succinimide derivatives containing 1,4 and 1,5 dicarbonyl scaffolds in good to excellent yields. The reaction tolerates variable substituents on both aldehydes and N-substituted itaconimides.

Application of sulfur ylides in 1,2-difunctionalization of arynes via insertion into a C-S sigma-bond - Ahire, Milind M.; Thoke, Mahesh B.; Mhaske, Santosh B. (Organic Letters, 2018)
A novel reactivity of sulfur ylides has been demonstrated in a transition-metal-free protocol to access ortho-substituted thioanisole derivatives by insertion of arynes into a C-S sigma-bond in moderate to good yields. The reaction involves the formation of C-C and C-S bonds and consecutive breaking of two C-S bonds under operationally mild reaction conditions.

Divergent synthesis of oxindolylidene acetates and spirooxindolopyrrolidones from arynes - Pandya, Virat G.; Mhaske, Santosh B. (Organic Letters, 2018)
A novel process for the preparation of various (E)-oxindolylidene acetates using arynes and carbamoylpropiolates has been developed. The utility of this protocol is also further extended to the one-pot synthesis of complex spirooxindolopyrrolidones. This method provides a milder and transition-metal-free access to both of the target scaffolds in moderate to good yields.

Isa-NHC-catalyzed intermolecular stetter reaction of aromatic aldehydes with maleimides: an efficient access to 3-aroylsuccinimides - Ahire, Milind M.; Mhaske, Santosh B. (Tetrahedron, 2018)
An intermolecular Stetter reaction of aromatic aldehydes with maleimides has been developed using thiazolylidene salt derived Isa-NHC as an efficient organocatalyst. The synthesized Stetter products "3-aroylsuccinimides" are important building blocks for the synthesis of natural products and bioactive compounds. The reaction conditions are mild, and various substituents on aromatic aldehyde and maleimide nitrogen were tolerated. (C) 2018 Elsevier Ltd. All rights reserved.

Ruthenium-catalyzed regioselective alkenylation/tandem hydroamidative cyclization of unmasked quinazolinones using terminal alkynes - Viveki, Amol B.; Mhaske, Santosh B. (Journal of Organic Chemistry, 2018)
Ruthenium-catalyzed amide directed C-sp2-H activation of the quinazolinone scaffold has been demonstrated, leading to the selective mono- or dialkenylation in moderate to good yields to achieve medicinally important stilbene containing quinazolinones. The terminal allcyne is utilized as a coupling partner, which resulted in the selective trans-alkene formation. Electron-deficient phenylacetylenes facilitate alkenylation followed by tandem hydroamidation of the newly generated trans double bond to provide novel quinazolinone alkaloids related to the Luotonine class of natural products.

Silver-mediated oxidative decarboxylative intramolecular asymmetric radical cyclization (C sp3 –C sp2 ) via memory of chirality: access to circumdatin alkaloids - Mahajan, Pankaj S.; Mhaske, Santosh B. (Organic Letters, 2018)
A novel silver-mediated oxidative decarboxylative intramolecular asymmetric radical cyclization has been developed to form a Csp3–Csp2 bond via memory of chirality. The application of the process has been demonstrated for the synthesis of the circumdatin class of alkaloids in high enantiopurity with retention of the configuration. The developed protocol is mild and works with an inexpensive silver catalyst in the absence of ligand, base, or additives. The involvement of a monoradical in the reaction has been established by trapping the radical intermediate.

Transition-metal-catalyzed reactions involving arynes - Dhokale, Ranjeet A.; Mhaske, Santosh B. (Synthesis-Stuttgart, 2018)
The plethora of transformations attainable by the transition-metal-catalyzed reactions of arynes has found immense contemporary interest in the scientific community. This review highlights the scope and importance of transition-metal-catalyzed aryne reactions in the field of synthetic organic chemistry reported to date. It covers transformations achieved by the combination of arynes and various transition metals, which provide a facile access to a biaryl motif, fused polycyclic aromatic compounds, different novel carbocycles, various heterocycles, and complex natural products. 1 Introduction 2 Insertion of Arynes 3 Annulation of Arynes 4 Cycloaddition of Arynes 5 Multicomponent Reactions of Arynes 6 Miscellaneous Reactions of Arynes 7 Total Synthesis of Natural Products Using Arynes 8 Conclusion
Keywords: annulation; arynes; Cycloaddition; Insertion; multicomponent; Natural products; Transition Metal

Ru-catalyzed regioselective cascade annulation of acrylamides with 2-alkynoates for the synthesis of various 6-Oxo nicotinic acid esters - Garad, Dnyaneshwar N.; Mhaske, Santosh B. (Journal of Organic Chemistry, 2019)
Ru-catalyzed regioselective cascade annulation of acrylamides with 2-alkynoates via aza-Michael/C-H activation sequence for the synthesis of various 6-oxo nicotinic acid esters is described. The regioselectivity of the protocol has been confirmed by performing silver mediated protodecarboxylation of the corresponding 6-oxo nicotinic acid to furnish 2-pyridone. The developed protocol is copper or silver salt-free and uses inexpensive, safe, and environmentally benign peroxide-based ``oxone'' as the sole oxidant. A redox-neutral version of the protocol is also demonstrated.

Stereoselective construction of deoxy-cruciferane alkaloids by NHC-catalyzed intramolecular annulation of homoenolate with quinazolinone - Ahire, Milind M.; Pol, Mahesh D.; Kavale, Dattatry S; Gonnade, Rajesh G.; Mhaske, Santosh B. (Organic & Biomolecular Chemistry, 2019)
Chiral N-heterocyclic carbene (NHC)-catalyzed intramolecular [3 + 2] annulation of enals with an unactivated imine moiety of quinazolinone via formal homoenolate cycloaddition has been demonstrated. It is an excellent approach for stereoselective syntheses of deoxy-cruciferane alkaloids comprising a biologically important pyrroloindoline scaffold. Notably, this is the first report on the NHC-catalyzed asymmetric intramolecular homoenolate annulation with cyclic N-acyl amidine.

Construction of unique SCF3-containing building blocks via allylic alkylation of Morita-Baylis-Hillman adducts - Halder, Priyanka; Pol, Mahesh D.; Ahire, Milind M.; Mhaske, Santosh B. (Organic & Biomolecular Chemistry, 2020)
Lewis base-catalyzed allylic alkylation of Morita-Baylis-Hillman adducts with alpha-SCF3 ketones has been demonstrated. The developed strategy provides efficient access to a series of highly functionalized scaffolds featuring trifluoromethanesufinyl motif on a stereogenic carbon.

Highly enantioselective synthesis of sitagliptin - Khopade, V. Kishor; Sen, Anirban; Birajdar, Rajkumar S.; Paulbudhe, Uday P.; Kavale, Dattatry S.; Shinde, Prashant S.; Mhaske, Santosh B.; Chikkali, Samir H. (Asian Journal of Organic Chemistry, 2020)
A highly enantioselective synthesis of sitagliptin, a potent DPP-4 inhibitor, is reported. Explicitly identified chiral FerroLANE ligands in the presence of rhodium catalyze the asymmetric hydrogenation of an enamine to yield sitagliptin with excellent enantioselectivity (98% ee). The process was scaled up to 5 g and the final product was isolated as a phosphate salt with >99% ee.
Keywords: asymmetric hydrogenation; catalysis; FerroLANE ligands; Rhodium; sitagliptin

Para-selective copper-catalyzed C(sp(2))-H amidation/dimerization of anilides via a radical pathway - Viveki, Amol B.; Garad, Dnyaneshwar N.; Gonnade, Rajesh G.; Mhaske, Santosh B. (Chemical Communications, 2020)
Copper-catalyzed amidation/dimerization of anilides via regioselective C(sp(2))-H functionalization is achieved. The para-selective amidation is accomplished on the anilide aromatic ring via a radical pathway leading to C-N bond formation in the presence of ammonium persulfate as a radical source/oxidant for the copper catalyst. The developed protocol tolerates a wide range of anilide substrates. The regioselectivity is confirmed by single-crystal X-ray studies.

Annulation of enals with carbamoylpropiolates via NHC-catalyzed enolate pathway: access to functionalized maleimides/iso-maleimides and synthesis of aspergillus FH-X-213 - Viveki, Amol B.; Pol, Mahesh D.; Halder, Priyanka; Sonavane, Sameer R.; Mhaske, Santosh B. (Journal of Organic Chemistry, 2021)
Herein we report the N-heterocyclic carbene (NHC)-catalyzed [3 + 2] annulation of alpha,beta-unsaturated aldehydes with carbamoylpropiolates via an unusual enolate pathway leading to the construction of highly functionalized maleimides or isomaleimides. The electronic effect imposed by the alkyl/aryl group present on the amide nitrogen of carbamoylpropiolates plays a crucial role in the selective formation of these important five-membered heterocyclic building blocks. The developed protocol is mild and tolerates a wide range of substituents on both substrates. The application of this protocol in the synthesis of the antibacterial natural product Aspergillus FH-X-213 has also been demonstrated.

Phosphine-free manganese(II)-catalyst enables acceptorless dehydrogenative coupling of alcohols with indoles - Yadav, Vinita; Balaraman, Ekambaram; Mhaske, Santosh B. (Advanced Synthesis & Catalysis, 2021)
Herein, an air-stable, molecularly defined NNN-Mn(II) pincer complex catalyzed acceptorless dehydrogenative coupling of alcohols with indoles is reported. A wide variety of symmetrical and unsymmetrical bis(indolyl)methane derivatives as well as some structurally important products such as Vibrindole A, Turbomycin B alkaloid, Antileukemic, and Anticancer agents were synthesized. Mechanistic studies illustrate the importance of the NH moiety in the complex and the crucial role of metal-ligand cooperation during catalysis.
Keywords: acceptorless dehydrogenation; Alcohol; Indole; manganese; phosphine-free

Photoactivatable prodrug for simultaneous release of mertansine and CO along with a BODIPY derivative as a luminescent marker in mitochondria: a proof of concept for NIR image-guided cancer therapy - Tiwari, Rajeshwari; Shinde, Prashant S.; Sreedharan, Sreejesh; Dey, Anik Kumar; Vallis, Katherine A.; Mhaske, Santosh B.; Pramanik, Sumit kumar; Das, Amitava (Chemical Science, 2021)
Controlled and efficient activation is the crucial aspect of designing an effective prodrug. Herein we demonstrate a proof of concept for a light activatable prodrug with desired organelle specificity. Mertansine, a benzoansamacrolide, is an efficient microtubule-targeting compound that binds at or near the vinblastine-binding site in the mitochondrial region to induce mitotic arrest and cell death through apoptosis. Despite its efficacy even in the nanomolar level, this has failed in stage 2 of human clinical trials owing to the lack of drug specificity and the deleterious systemic toxicity. To get around this problem, a recent trend is to develop an antibody-conjugatable maytansinoid with improved tumor/organelle-specificity and lesser systematic toxicity. Endogenous CO is recognized as a regulator of cellular function and for its obligatory role in cell apoptosis. CO blocks the proliferation of cancer cells and effector T cells, and the primary target is reported to be the mitochondria. We report herein a new mitochondria-specific prodrug conjugate (Pro-DC) that undergoes a photocleavage reaction on irradiation with a 400 nm source (1.0 mW cm(-2)) to induce a simultaneous release of the therapeutic components mertansine and CO along with a BODIPY derivative (BODIPY(PPH3)(2)) as a luminescent marker in the mitochondrial matrix. The efficacy of the process is demonstrated using MCF-7 cells and could effectively be visualized by probing the intracellular luminescence of BODIPY(PPH3)(2). This provides a proof-of-concept for designing a prodrug for image-guided combination therapy for mainstream treatment of cancer.

Construction of tetrahydrobenzo[f]quinoline scaffolds via polar [4+2]-Cycloaddition reaction with arynes as dienophiles - Pandya, Virat G.; Mhaske, Santosh B. (Tetrahedron Letters, 2022)
A transition-metal-free route has been developed for the direct synthesis of biologically significant tetrahydrobenzo[f]quinoline scaffolds. The reaction features polar [4 + 2] Diels-Alder cycloaddition reaction of arynes with a well-designed diene N-Boc protected vinyl tetrahydropyridine, followed by the isomerisation of the double bond leading to the formation of tetrahydrobenzo[f]quinoline scaffolds in good to moderate yields.
Keywords: Aryne; Diels-Alder; Diene; Tetrahydrobenzo[ f ]quinoline

Nickel-catalyzed direct synthesis of N-substituted indoles from amino alcohols and alcohols - Yadav, Vinita; Jagtap, Sayali G.; Balaraman, Ekambaram; Mhaske, Santosh B. (Organic Letters, 2022)
A one-pot cascade approach for the synthesis of N substituted indoles from amino alcohols and alcohols under additive and base-free conditions with the liberation of water as the only stoichiometric byproduct is reported. The commercially available bench-stable Ni(OTf)2 salt in combination with 1,2-bis(dicyclohexylphosphino)ethane (dcype) is very effective for this unprecedented catalytic transformation. A broad range of substrates including aromatic and aliphatic primary alcohols, cyclic and acyclic secondary alcohols, and various substituted 2-aminophenyl ethyl alcohols are employed in the reaction conditions to provide a diverse range of N-alkylated indoles. Mechanistic studies revealed that the reaction proceeds through tandem N-alkylation via hydrogen autotransfer followed by the cyclization of N-alkylated alcohol intermediate.

Enantioselective intramolecular decarboxylative C-H bond func-tionalization of quinazolinones with amino acids by visible light photoredox catalysis - Sonavane, Sameer R.; Mhaske, Santosh B. (Chemistry-An Asian Journal, 2023)
The direct visible light-mediated intramolecular decarboxylative C-H functionalization of Csp(2)-H bond adjacent to the nitrogen of a heteroarene has been achieved by iridium-catalyzed photodecarboxylative radical cyclization. This method offers rapid entry to the synthesis of quinazolinone scaffolds from easily accessible starting materials. The newly developed protocol is mild, operationally simple, oxidant free and general. The utility of this unique Csp(3)-Csp(2) bond forming reaction has been demonstrated in the syntheses of Circumdatin, Sclerotigenine and Benzomalvin A class of quinazolinone natural products and their congeners. The present work represents an interesting example of use of memory of chirality in decarboxylative C-C bond forming enantioselective photoredox reaction.
Keywords: C-H functionalization; memory of chirality; Minisci reaction; photodecarboxylative cyclization; photoredox catalysis; quinazolinone alkaloid; Radical

PIDA-mediated N-N bond formation to access pyrazolidine-3,5-diones: a novel process for uricosuric agents G-25671 and sulfinpyrazone - Halder, Priyanka; Mhaske, Santosh B. (Chemical Communications, 2023)
Traditionally, toxic and expensive hydrazine building blocks are required to construct pharmaceutically important pyrazolidine-3,5-diones. Herein, we have described a novel method for their synthesis based on metal-free oxidative dehydrogenative N-N bond formation by PIDA-mediated reaction of easily accessible dianilide precursors. The developed mild reaction protocol features a good functional group tolerance and scalability. The application of this method is demonstrated by offering a unique route for the synthesis of uricosuric agents G-25671 and sulfinpyrazone from inexpensive starting material aniline via smooth functionalization of the well-designed diversity-oriented cyclopropyl key intermediate.

Functionalized quinolones and isoquinolones via 1,2-difunctionalization of arynes: synthesis of antagonist agent AS2717638 and floxacin key intermediates - Mahale, Sachin D.; Prasad, Anamika; Mhaske, Santosh B. (Chemical Communications, 2024)
Quinolones and isoquinolones are privileged scaffolds in synthetic/medicinal chemistry and drug discovery due to their unique chemical structures and intrinsic properties. Herein, we reveal a transition-metal-free approach for their synthesis from the reaction of dimethyl-2-((phenylamino)methylene)malonate with aryne precursors under mild conditions. The substrate scope is broad, accommodating a wide range of functional groups. The synthetic utility of the developed protocol has been demonstrated in the total synthesis of the potent antagonist agent AS2717638 and key intermediates of floxacin congeners. The gram-scale experiments illustrate its synthetic potential.

Regio- and stereoselective construction of 1,3,5-triaroylcyclohexanes via KO t Bu-mediated cyclotrimerization of aryl vinyl ketones - Mahale, Sachin D.; Yadav, Vinita; Gonnade, Rajesh G.; Mhaske, Santosh B. (Journal of Organic Chemistry, 2024)
Herein, we disclose a simple one-pot method for an efficient regio- and stereoselective synthesis of 1,3,5-triaroylcyclohexanes from aryl vinyl ketones using potassium tert-butoxide. The developed protocol allows the construction of various symmetrically substituted cyclohexanes in good to excellent yields. The major product 2 also can be converted to the product 3 (all equatorial) conveniently by acid catalysis. This protocol features a good substrate scope and functional group compatibility.

Atom-economical and scalable asymmetric synthesis of daridorexant key starting material (S)-2-methylproline via the memory of chirality - Bhatt, Gaurang J.; Kumar, Shubham; Mhaske, Santosh B. (Organic Process Research & Development, 2025)
alpha-Methylproline is a key starting material (KSM) for important drugs, such as Daridorexant, Veliparib, Trofinetide, Enlicitide chloride, and Usnoflast. A practical and scalable asymmetric synthesis of (S)-2-methylproline and its derivatives has been disclosed here using a diketopiperazine intermediate-based strategy that leverages the memory of chirality. Commencing from an inexpensive starting material, l-proline, it proceeds through dimerization and alkylation, followed by hydrolysis under mild conditions, avoiding column chromatography to furnish enantiomerically pure (S)-2-methylproline.HCl, which was also converted to (S)-Boc-2-methylproline and (S)-2-methylproline methyl ester.HCl. In contrast to prior multistep approaches, which rely on expensive chiral auxiliaries and hazardous reagents, this concise three-step route offers operational simplicity, scalability, and superior stereochemical control, making it an attractive method for the synthesis of proline-derived building blocks for peptidomimetics and pharmaceutical applications.
Keywords: alpha-methylproline; atom economy; memoryof chirality; Stereoselective

NHC-catalyzed allylation of aldehydes with MBH carbonates and their michael addition-elimination-cope rearrangement cascade: a route to rac-sacubitril - Kale, Tushar B.; Jagtap, Sayali G.; Mhaske, Santosh B. (Organic Letters, 2025)
We report herein a novel NHC-catalyzed transition-metal-free chemoselective allylation of aldehydes with Morita-Baylis-Hillman (MBH) carbonates using an inorganic base. Fascinatingly, the use of an organic base follows a different mechanism, leading to highly functionalized 1,5-dienes via a Michael addition-elimination reaction followed by [3,3]-sigmatropic Cope rearrangement. The described method harnesses a new Csp2-Csp3 bond to access alpha-methylene-gamma-oxo-gamma-substituted ester derivatives paving a way to facile synthesis of potent natural products and active pharmaceutical ingredients (APIs). A broad range of aromatic and aliphatic aldehydes with MBH carbonates was employed to provide a variety of interesting butanoate and dienyl ketone scaffolds in good to excellent yields. This chemistry has been extended to the efficient syntheses of rac-sacubitril API and gamma-butyrolactone scaffold, which is a privileged core present in many natural products and APIs

Organophotoredox-catalyzed decarboxylative C-O/N/S bond formation: access to ampakine APIs and quinazolinone alkaloids - Sonavane, Sameer R.; Kale, Tushar B.; Bhatt, Gaurang J.; Mhaske, Santosh B. (Organic Letters, 2025)
This study describes a novel and general protocol featuring organophotoredox-catalyzed intramolecular decarboxylative construction of carbon-heteroatom (oxygen, nitrogen, and sulfur) bonds, enabling direct access to ampakine APIs (CX-614 and CX-554), quinazolinone alkaloids (deoxyvasicinone and mackinazolinone), and thiazinone scaffolds as well as their congeners with broad functional group tolerance and scalability. Mechanistic studies suggest a radical-polar crossover pathway via single-electron oxidation.